Current trends in the treatment of infantile spasms - Chang-Yong Tsao (Dove Medical Press, 2009)
Chang-Yong TsaoClinical Pediatrics and Neurology, The Ohio State University, College of Medicine, Columbus, Ohio, USAAbstract: Infantile spasms are an epilepsy syndrome with distinctive features, including age onset during infancy, characteristic epileptic spasms, and specific electroencephalographic patterns (interictal hypsarrhythmia and ictal voltage suppression). Adrenocorticotropic hormone (ACTH) was first employed to treat infantile spasms in 1958, and since then it has been tried in prospective and retrospective studies for infantile spasms. Oral corticosteroids were also used in a few studies for infantile spasms. Variable success in cessation of infantile spasms and normalization of electroencephalograms was demonstrated. However, frequent significant adverse effects are associated with ACTH and oral corticosteroids. Vigabatrin has been used since the 1990s, and shown to be successful in resolution of infantile spasms, especially for infantile spasms associated with tuberous sclerosis. It is associated with visual field constriction, which is often asymptomatic and requires perimetric visual field study to identify. When ACTH, oral corticosteroids, and vigabatrin fail to induce cessation of infantile spasms, other alternative treatments include valproic acid, nitrazepam, pyridoxine, topiramate, zonisamide, lamotrigine, levetiracetam, felbamate, ganaxolone, liposteroid, thyrotropin-releasing hormone, intravenous immunoglobulin and a ketogenic diet. Rarely, infantile spasms in association with biotinidase deficiency, phenylketonuria, and pyridoxine-dependent seizures are successfully treated with biotin, a low phenylalanine diet, and pyridoxine, respectively. For medically intractable infantile spasms, some properly selected patients may have complete cessation of infantile spasms with appropriate surgical treatments.Keywords: infantile spasms, adrenocorticotropic hormone, oral corticosteroids, vigabatrin